Arabidopsis thaliana mTERF proteins: evolution and functional classification - Kleine, Tatjana (Frontiers in Plant Science, 2012)
Organellar gene expression (OGE) is crucial for plant development, photosynthesis and respiration, but our understanding of the mechanisms that control it is still relatively poor. Thus, OGE requires various nucleus-encoded proteins that promote transcription, splicing, trimming and editing of organellar RNAs, and regulate translation. In metazoans, proteins of the mitochondrial Transcription tERmination Factor (mTERF) family interact with the mitochondrial chromosome and regulate transcriptional initiation and termination. Sequencing of the Arabidopsis thaliana genome led to the identification of a diversified MTERF gene family but, in contrast to mammalian mTERFs, knowledge about the function of these proteins in photosynthetic organisms is scarce. In this hypothesis article, I show that tandem duplications and one block duplication contributed to the large number of MTERF genes in A. thaliana, and propose that the expansion of the family is related to the evolution of land plants. The MTERF genes - especially the duplicated genes - display a number of distinct mRNA accumulation patterns, suggesting functional diversification of mTERF proteins to increase adaptability to environmental changes. Indeed, hypothetical functions for the different mTERF proteins can be predicted using co-expression analysis and gene ontology annotations. On this basis, mTERF proteins can be sorted into five groups. Members of the “chloroplast” and “chloroplast-associated” clusters are principally involved in chloroplast gene expression, embryogenesis and protein catabolism, while representatives of the “mitochondrial” cluster seem to participate in DNA and RNA metabolism in that organelle. Moreover, members of the “mitochondrion-associated” cluster and the “low expression” group may act in the nucleus and/or the cytosol. As proteins involved in OGE and presumably nuclear gene expression, mTERFs are ideal candidates for the coordination of the expression of organelle and nuclear genomes.